2022
DOI: 10.1186/s12885-022-10122-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a fatty acid metabolism-related lncRNA signature as a predictor for prognosis and immunotherapy in patients with liver cancer

Abstract: Background Fatty acid (FA) metabolism is considered the emerging cause of tumor development and metastasis, driving poor prognosis. Long non-coding RNAs (lncRNAs) are closely related to cancer progression and play important roles in FA metabolism. Thus, the discovery of FA metabolism-related lncRNA signatures to predict outcome and immunotherapy response is critical in improving the survival of patients with hepatocellular carcinoma (HCC). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 70 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Increasing evidence has confirmed that lncRNAs are essential in regulating various biological processes, including cell proliferation, differentiation, apoptosis, migration, invasion, and the cell cycle 31,32 . Recently, the role of lncRNAs in the diagnosis and treatment of liver diseases has also been recognized 33,34 . It has also been reported that lncRNAs participate in gene regulation during ischemia–reperfusion injury of important organs such as the brain 35,36 and the heart 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has confirmed that lncRNAs are essential in regulating various biological processes, including cell proliferation, differentiation, apoptosis, migration, invasion, and the cell cycle 31,32 . Recently, the role of lncRNAs in the diagnosis and treatment of liver diseases has also been recognized 33,34 . It has also been reported that lncRNAs participate in gene regulation during ischemia–reperfusion injury of important organs such as the brain 35,36 and the heart 37 …”
Section: Discussionmentioning
confidence: 99%
“…31,32 Recently, the role of lncRNAs in the diagnosis and treatment of liver diseases has also been recognized. 33,34 It has also been reported that lncRNAs participate in gene regulation during ischemia-reperfusion injury of important organs such as the brain 35,36 and the heart. 37 Nevertheless, research on lncRNAs expression profiles in liver transplantation is still limited and is mainly derived from animal or in vitro models of liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed exclusive MetNorm regulons were enriched to lipid metabolism, cholesterol/sterol homeostasis, and cell cycle signaling, suggesting their role in cell proliferation and castration resistance in mCRPC. Two of these MRs (HAND2‐AS1 and LINC00261) are described in the literature associated with the maintenance of intracellular cholesterol 52 and fatty acid metabolism, 53 respectively. Several findings have supported the involvement of cholesterol in cell proliferation by maintaining membrane integrity and signal transduction 54 .…”
Section: Discussionmentioning
confidence: 99%
“…An in silico study identified an FA metabolism-related lncRNA signature which categorized patients from two online datasets on the basis of a high or low FA metabolic score. Notably, patients with a lower FA metabolic score presented a higher immune cell infiltration score, an upregulation of critical immune checkpoint inhibitor genes, and a higher tumor immune dysfunction and exclusion (TIDE) score, suggesting that this patient subgroup may experience immune escape and may have a lower probability of benefit from immunotherapy [104]. Similarly, a signature based on the expression of the lncRNA SNHG1 and on its target genes FANCD2 (FA complementation group D2) and G6PD (glucose 6 phosphate dehydrogenase), the expression of which is increased due to miR-199a sponging activity, displayed an association with poorer OS in patients within the high-risk group.…”
Section: Noncoding Rnas Affect Immunotherapy Response By Interfering ...mentioning
confidence: 99%